The Effect of Peer Learning to Nursing Care Knowledge and Occupational Stress of the Novice Nurse - I Made Rio Dwijayanto; Catharina Dwiana Wijayanti; Sudibyo Supardi (Indonesian Journal of Health Research, 2018)
Background. The transition period for novice nurses is the transition of roles as students become professional nurses. Conflict between expectations and the reality of the roles faced can cause stress. The peer learning learning model is a method of learning with peers that aims to develop skills, ways of thinking, solving problems, giving feedback and communicating with others. This study aims to determine the effect of peer learning on nursing care knowledge and work stress on novice nurses in hospital in Jakarta. Methods. This study used a quasi-experimental pretest-posttest control group design. The novice nurse research sample was divided into two groups, namely the intervention group and the control group with the number of each of 35 respondents using purposive sampling technique. Data collection tools use knowledge instruments about nursing care and Nursing Students Clinical Stress Scale. Data analysis using the Wilcoxon test, Chi-Square test, and Multivariate logistic regression. Results. The results showed differences in the quality of knowledge of nursing care and work stress before and after the implementation of peer learning for 3 times in 3 weeks had the possibility of knowledge increased 13 times compared to clinical nurses who did not implement peer learning and had the possibility of reducing work stress 27 times compared to clinical nurses who do not carry out peer learning. Conclusion. The implementation of peer learning is proven to influence the knowledge of nursing care and occupational stress of the novice nurse. It is recommended to carry out scheduled peer learning programs.